2002
DOI: 10.1038/416334a
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen protects FKBP12.6 null mice from cardiac hypertrophy

Abstract: FK506 binding proteins 12 and 12.6 (FKBP12 and FKBP12.6) are intracellular receptors for the immunosuppressant drug FK506 (ref. 1). The skeletal muscle ryanodine receptor (RyR1) is isolated as a hetero-oligomer with FKBP12 (ref. 2), whereas the cardiac ryanodine receptor (RyR2) more selectively associates with FKBP12.6 (refs 3, 4, 5). FKBP12 modulates Ca2+ release from the sarcoplasmic reticulum in skeletal muscle and developmental cardiac defects have been reported in FKBP12-deficient mice, but the role of FK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
208
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(224 citation statements)
references
References 31 publications
12
208
2
2
Order By: Relevance
“…Transgenic overexpression of phospholamban, TNF-a, b2AR, NCX showed a gender-related discrepancy in the cardiac phenotype in which the more severe phenotype was observed in males [38][39][40][41]. Similarly, gene disruption of FKBP12.6, phospholamban, and ERa revealed a cardiac phenotype with male preponderance [42][43][44]. Studies with patients hospitalized for acute heart failure in the EuroHeart Failure Survey II revealed that men had DCM more frequently than women [45].…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic overexpression of phospholamban, TNF-a, b2AR, NCX showed a gender-related discrepancy in the cardiac phenotype in which the more severe phenotype was observed in males [38][39][40][41]. Similarly, gene disruption of FKBP12.6, phospholamban, and ERa revealed a cardiac phenotype with male preponderance [42][43][44]. Studies with patients hospitalized for acute heart failure in the EuroHeart Failure Survey II revealed that men had DCM more frequently than women [45].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by a protective role of estrogens in the hypertrophic response and the evidence that exposure of cardiac myocytes to androgen results in hypertrophy. 32,33 Furthermore, the HCM phenotype is influenced by sex hormone receptor variants. 34 However, in our study, the sex effect in the probands was less clear, with females tending to be more heavily affected at young age, although one must acknowledge that there was considerable overlap between males and females in this group (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is considerable debate regarding the role of FKBP12 in TGF-␤ signaling, since many members of FKBP are found to be expressed ubiquitously. Therefore, it is still unclear which isoform of FKBP is involved in TGF-␤ signaling in T cells (51)(52)(53)(54). In the absence of TGF-␤1 there could be disequilibria of TGF-␤ type I receptorassociated FKBPs, resulting in leaky Ca 2ϩ release channels.…”
Section: Discussionmentioning
confidence: 99%